2016
DOI: 10.1097/qai.0000000000001129
|View full text |Cite
|
Sign up to set email alerts
|

Preexposure Prophylaxis for HIV Prevention in a Large Integrated Health Care System: Adherence, Renal Safety, and Discontinuation

Abstract: Background Placebo-controlled and open-label studies have demonstrated the safety and efficacy of daily oral preexposure prophylaxis (PrEP) in preventing HIV infection, but data are limited on real-world PrEP use. Methods We conducted a cohort study from July 2012 through June 2015 of Kaiser Permanente Northern California members initiating PrEP. We assessed pharmacy refill adherence and discontinuation, decreases in estimated glomerular filtration rate (eGFR), and sexually transmitted infection (STI)/HIV in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
249
2
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 255 publications
(265 citation statements)
references
References 36 publications
10
249
2
4
Order By: Relevance
“…These data and reports of high adherence for PrEP elsewhere(23, 24) are encouraging that PrEP adherence among individuals who desire it will be high enough to realize effective HIV prevention outside of clinical trials.…”
Section: Discussionmentioning
confidence: 79%
“…These data and reports of high adherence for PrEP elsewhere(23, 24) are encouraging that PrEP adherence among individuals who desire it will be high enough to realize effective HIV prevention outside of clinical trials.…”
Section: Discussionmentioning
confidence: 79%
“…A study of men who have sex with men found retention in PrEP care at three and six months to be 72% and 57%, respectively, higher than our study’s estimates (Chan et al, 2016). Another found that women were more likely to discontinue PrEP compared with men (Marcus et al, 2016). As cost and lack of insurance coverage have been suggested as barriers to PrEP use, we would have expected greater retention among women as PrEP coverage is nearly universal in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of insurance coverage leading to medication non-adherence has been associated with acquisition of HIV infection in cohorts of PrEP patients. 21 …”
Section: Discussionmentioning
confidence: 99%